The Implementation of the Principles of Good Corporate Governance in the Merger Process of Public Companies - Yovanka Angela Siregar; Rasji (Program magister Kenotariatan Fakultas Hukum Universitas Lambung Mangkurat, 2025)
Global economic dynamics have encouraged public companies to engage in mergers as a corporate strategy to enhance competitiveness and operational efficiency. The merger between PT Indosat Tbk and PT Hutchison 3 Indonesia exemplifies a strategic action that requires comprehensive implementation of Good Corporate Governance (GCG) principles to ensure transparency, accountability, and legal certainty for all stakeholders. This study aims to analyze the application of GCG principles in the merger process of public companies and evaluate their conformity with Indonesian legal regulations. The research applies a normative juridical method by examining primary and secondary legal materials, including Law Number 40 of 2007 on Limited Liability Companies and regulations issued by the Financial Services Authority. The findings indicate that the Indosat–Hutchison merger has implemented GCG principles through transparent disclosure, independent valuation, and protection of minority shareholders’ rights. The implementation strengthens investor confidence and highlights the essential role of legal and notarial professionals in ensuring corporate compliance during mergers.